Advanced cognitive training for breast cancer survivors: a randomized controlled trial - Von Ah, Diane (2012)
The purpose of this study was to evaluate the preliminary efficacy and satisfaction/acceptability of training in memory or speed of processing versus wait-list control for improving cognitive function in breast cancer survivors. 82 breast cancer survivors completed a three-group randomized, controlled trial. Primary outcomes were objective neuropsychological tests of memory and speed of processing. Secondary outcomes were perceived cognitive functioning, symptom distress (mood disturbance, anxiety, and fatigue), quality of life, and intervention satisfaction/acceptability. Data were collected at baseline, post-intervention, and 2-month follow-up. Using repeated-measures mixed-linear ANCOVA models, each intervention was compared to wait-list control while adjusting for age, education, and baseline measures. The effect sizes for differences in means and the reliable improvement percentage were reported. The results show that domain-specific effects were seen for both interventions: memory training improved memory performance at 2-month follow-up (p = 0.036, d = 0.59); speed of processing training improved processing speed post-intervention (p = 0.040, d = 0.55) and 2-month follow-up (p = 0.016; d = 0.67). Transfer effects to non-trained domains were seen for speed of processing training with improved memory post-intervention (p = 0.007, d = 0.75) and 2-month follow-up (p = 0.004, d = 0.82). Both interventions were associated with improvements in perceived cognitive functioning, symptom distress, and quality of life. Ratings of satisfaction/acceptability were high for both interventions. It was concluded that while both interventions appeared promising, speed of processing training resulted in immediate and durable improvements in objective measures of processing speed and verbal memory. Speed of processing training may have broader benefits in this clinical population.